2016
DOI: 10.14302/issn.2328-0182.japst-15-855
|View full text |Cite
|
Sign up to set email alerts
|

Proximate, Mineral And Antinutrient Compositions Of Natural Cocoa Cake, Cocoa Liquor And Alkalized Cocoa Powders

Abstract: An investigation into the proximate, mineral and antinutitional constitutents of natural cocoa powder (NCP), natural cocoa liquor (NCL) and alkalized cocoa powder (ACP) was carried out. Other parameters investigated were: energy values as contributed to the total metabolisable energy by protein, fat and carbohydrate and the energy percentages; calculated mineral quality parameters; mineral bioavailability as predicted by Ca: Phy, The three samples, NCP, NCL and ACP had proximate levels (g/100g) as: total ash, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…Compound 13 showed a fragment ion at m/z 72 and it was assigned to Val-Val, whereas compound 22 was tentatively assigned to Arg-Thr since this compound exhibited fragments at m/z 175 and m/z 120 that correspond to the loss of arginine and threonine, respectively. The trend of both dipeptides was to decrease their amount as the alkalization degree increased, which is in agreement with previous literature where it has been described that the content of proteins, peptides, and amino acids decreases in alkalized cocoa samples since this process changes the media leading to the degradation of this kind of compounds (Adeyeye, 2016;Méndez-Albores et al, 2013;Odus & Longe 1998). The ion at m/z 142 ([M+H] + ) was tentatively identified as L-Hypoglycin A (compound 20).…”
Section: Tablesupporting
confidence: 91%
See 1 more Smart Citation
“…Compound 13 showed a fragment ion at m/z 72 and it was assigned to Val-Val, whereas compound 22 was tentatively assigned to Arg-Thr since this compound exhibited fragments at m/z 175 and m/z 120 that correspond to the loss of arginine and threonine, respectively. The trend of both dipeptides was to decrease their amount as the alkalization degree increased, which is in agreement with previous literature where it has been described that the content of proteins, peptides, and amino acids decreases in alkalized cocoa samples since this process changes the media leading to the degradation of this kind of compounds (Adeyeye, 2016;Méndez-Albores et al, 2013;Odus & Longe 1998). The ion at m/z 142 ([M+H] + ) was tentatively identified as L-Hypoglycin A (compound 20).…”
Section: Tablesupporting
confidence: 91%
“…Several works have investigated the change in the composition of alkalized cocoa (Valverde-García et al, 2020). In general, these works are focused on the determination of: (i) the total content of polyphenols (Andres-Lacueva et al, 2008;Gu et al, 2006;Gültekin-Özgüven et al, 2016;Hurst et al, 2011;Jolić et al, 2011;Kofink et al, 2007;Li et al, 2014;Miller et al, 2008;Payne et al, 2010;Quelal-Vásconez et al, 2020;Rodriguez et al, 2009;Stanley et al, 2015;Stark & Hofmann, 2006;Todorovic et al, 2017), (ii) the mineral content (Adeyeye et al, 2016) (iii) the volatile composition (Alasti et al, 2019(Alasti et al, , 2020Li et al, 2012) or (iv) the effect of alkalization on Maillard products (Tas ¸ & Gökmen, 2016). However, these studies are based on the determination of a specific class of compounds and just a few articles have reported the characterization of a wide variety of compounds including volatile and nonvolatile compounds (Li et al, 2012;Sioriki et al, 2022) or the identification of new compounds as a result of alkalization treatment (Germann et al, 2019a(Germann et al, , 2019b.…”
Section: Introductionmentioning
confidence: 99%
“…In general, fat-reduced cocoa powders showed a major carbohydrates content. Despite this, some authors have reported lower fat values in alkalized cocoa powders (4.93 g/100 g) [ 44 ], probably due to the hydrolysis and saponification of triglycerides [ 8 ]; in this study, this effect was not observed.…”
Section: Resultscontrasting
confidence: 72%
“…Petit et al [ 45 ] reported protein values between 18.1 to 24.4 g/100 g of cocoa, with this value being higher in samples with lower fat content. In the study of Adeyeye [ 44 ], a content of 10.9 g/100 g of alkalized cocoa powder was observed. That diminution of protein content could be due to oxidative destruction by deamination [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…These colours are used to boost the flavour and appearance of various food products and are therefore important parameters for food manufacturers. Reports from various cocoa processing industries in Nigeria indicated that cocoa powders of varying pH are produced according to the customer's specifications (Adeyeye, 2016).…”
Section: Physicochemical Properties Of the Dutched Cocoamentioning
confidence: 99%